"The Effects of Cognitive Behavioral Therapy on Academic Adjustment among Jordanian Students" - AL-MSEIDIN, Kholoud I.; AL-ZU'BI, Mohammad A. (Journal of evidence-based psychotherapies, 2021)
"This study aimed to investigate the effectiveness of cognitive behavioural therapy (CBT) as a counselling program intervention for Academic adjustment. In the experimental investigation, data was collected from a total of 68 low-achieving female students from one school in Amman city. The students in the experimental group were observed to complement their regular counselling for academic adjustment with CBT. The researchers used Academic adjustment scale (AAS) at pre- and post-tests. The duration of the study was 16 weeks of two sessions weekly, in which pre- and post-tests were included. ANCOVA was used to explore the findings of the current study. The findings demonstrated that low-achieving female students in the experimental group showed better academic adjustment than female students in the control group. The results have significance for reform the counselling educational policies in the Jordanian Ministry of education based on the importance of CBT-Intervention in educational counselling. Additionally, the study suggested relevant recommendations for future research."